Sinkronisasi Pengawasan CSR dalam Hukum Positif Indonesia - Nanda Melinia Safitri; Surya Anoraga; Fitria Esfandiari (Universitas Muhammadiyah Malang, 2022)
Since CSR has become an obligation for companies through Law Number 40 of 2007 concerning Limited Liability Companies. However, in its implementation there are still many problems. One of them is the regulation of CSR which has been implicitly regulated in various sectoral laws. So the problem that will be studied in this paper is how to synchronize the supervision of Corporate Social Responsibility (CSR) in the Limited Liability Company Law, Investment Law, Government Regulation No. 47 of 2012, as well as Article 23 and Article 24 of Malang Regency Regulation No. 1 of 2013. The research method used in this paper uses a normative juridical research type, using a statutory approach, a conceptual approach, and a comparative approach. The PT Law and the PM Law have different definitions regarding CSR, although both laws require the implementation of CSR, both have not provided clear regulations regarding the mechanism for monitoring CSR implementation. Then based on the mandate in Article 74 paragraph (4) of the Company Law, PP No. 47 of 2012, the establishment is intended to clarify the implementation of CSR but in fact the articles contained in the PP also do not accommodate the supervision of CSR implementation. Although it is not regulated in the Law and PP, the Malang Regency Regulation clearly regulates the supervision of CSR implementation. In this study, it is concluded that the various regulations are synchronized, namely in terms of implementation accountability, sanctions, and regulations for monitoring the implementation of CSR. Therefore, the government needs to form a separate law that accommodates CSR comprehensively along with the mandate of establishing a CSR supervisory body whose job is to oversee the implementation of CSR, giving executive authority to impose sanctions on those who do not carry out CSR.